Effect of a combined oral contraceptive on patency of arterial anastomosis in a female rat model. Issue 7 (25th August 2015) - Dadaci, Mehmet; Oztekin, Can; Oztekin, Pelin Seher; Sargon, Mustafa Fevzi; Ozgur, Figen
<x xml:space="preserve">Abstract</x> Background Oral contraceptives, which may lead to thrombotic events, are widely used drugs by women in reproductive age, some of whom might need emergent or elective microsurgical intervention. This study was planned to investigate the effects of combined oral contraceptives (COC) on arterial anastomosis patency in female rat model. Methods A third generation COC (ethinyl estradiol and desogestrel) was used in this study. A total of 50 female Wistar albino rats were included. The rats were divided into two groups. Experimental group received 0.03 mg ethinyl estradiol/0.15 mg desogestrel with gastric catheter for 20 days before the surgery. Afterward, the femoral arteries of all rats were divided and anastomosed. The patency of the anastomoses were assessed surgically (at 15 min, 7th day) and radiologically with Doppler ultrasonography (at 3rd and 7th days). The samples were examined using light microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Results The early patency assessed in the 15th min showed arterial flow in all rats. But at the 7th day 68% of the anastomosis were patent in the COC group while 100% of the anastomosis were patent in the control group as demonstrated surgically and radiologically (P = 0.004). Microscopic examination showed an increase in cytoplasmic organelles and activation of endothelial cells in all rats in the experimental group that received COCs. Conclusion The present study demonstrated the negative effects of the use of COCs on anastomosis patency in rats. © 2015 Wiley Periodicals, Inc. Microsurgery 35:553–559, 2015.